2019
DOI: 10.1537/ase.190303
|View full text |Cite
|
Sign up to set email alerts
|

Diachronic changes in linear enamel hypoplasia during the Edo period (1603–1867), Japan

Abstract: Linear enamel hypoplasia (LEH) is a useful indicator of childhood health. This study aimed at investigating whether there was any diachronic change in LEH occurrence during the Edo period (1603-1867). The Edo period, which experienced no major transition in subsistence and had no largescale contact with foreign population, did undergo various social changes that could have affected childhood health status. The skeletal remains of 144 adult individuals recovered from seven burial sites in Tokyo were examined. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Nakayama (2016) tried to reveal the association between the LEH occurrence and social status in 18 th -to 19 th -century Japanese populations. The same author also attempted to study diachronic change in LEH occurrence during the Edo period (Nakayama, 2019). Oyamada et al (2012) revealed a difference in LEH incidence between females and males of Edo-period Japanese as well.…”
Section: Advance Publication Brief Communicationmentioning
confidence: 99%
“…Nakayama (2016) tried to reveal the association between the LEH occurrence and social status in 18 th -to 19 th -century Japanese populations. The same author also attempted to study diachronic change in LEH occurrence during the Edo period (Nakayama, 2019). Oyamada et al (2012) revealed a difference in LEH incidence between females and males of Edo-period Japanese as well.…”
Section: Advance Publication Brief Communicationmentioning
confidence: 99%